A multi‐level coordinated scheduling strategy for shared energy storage systems under electricity spot and ancillary service markets - Qing Dou; Xiang Gao; Yuheng Wu; Yu Chen; Rui Xie; Jialin Chen (IET Renewable Power Generation)
Abstract This paper proposes a multi‐level coordinated scheduling strategy for shared energy storage systems (SESS) under electricity spot and ancillary service markets to maximize the overall operational profit. At the upper level, an optimal day‐ahead bidding model is formulated to allocate optimal capacities of SESS for engaging in electricity transactions and offering peak shaving reserve over the scheduling horizon. Then, a joint market clearing model is presented to simultaneously optimize awarded capacities of SESS and marginal prices of electricity spot and ancillary service markets at the middle level. Furthermore, the lower level aims to correct the coordinated scheduling strategy for minimizing the intra‐day scheduling cost under the uncertainty of renewable energy sources and load demand. Finally, a linear relaxation method is applied to transform the proposed strategy into a mixed‐integer linear programming problem for enhancing the computation efficiency. Comparative case studies have validated the superior performance of the proposed strategy for better utilization of available storage capacity and arbitrage maximization.